The Impact of a Scramble-Based Cooperative Learning Model Using Video Media on Student Learning Outcomes - Riswan Aradea; Slamet Cahyono; Rambat Nur Sasongko; Muhammad Kristiawan; Neta Dian Lestari (AL-ISHLAH: Jurnal Pendidikan, 2022)
The goal of this research was to see how the scramble-type cooperative learning model based on video media affected student learning outcomes in management accounting courses. The respondents in this study were undergraduate students at Palembang University, consisting of 36 students for the experimental class and 34 students for the control class. The experimental technique is employed. The test is the data-collecting instrument. According to the study's findings, 61.12 percent of students met good criteria, 19.44 percent met very good criteria, and 19.44 percent met sufficient criteria during the teaching and learning process employing a scramble-type cooperative learning model based on video media. And the experimental class's average learning results are 80.42. In traditional learning models, 73.52 percent of the criteria are sufficient, 17.65 percent are less criteria, 5.89 percent are good criteria, and 2.94 percent are less criteria. The scramble-based cooperative learning model using video media was effective for student learning outcomes